Unmethylated Insulin DNA Is Elevated After Total Pancreatectomy With Islet Autotransplantation: Assessment of a Novel Beta Cell Marker. Issue 4 (24th October 2016) - Bellin, M. D.; Clark, P.; Usmani‐Brown, S.; Dunn, T. B.; Beilman, G. J.; Chinnakotla, S.; Pruett, T. L.; Ptacek, P.; Hering, B. J.; Wang, Z.; Gilmore, T.; Wilhelm, J. J.; et al.
Abstract : Beta cell death may occur both after islet isolation and during infusion back into recipients undergoing total pancreatectomy with islet autotransplantation (TPIAT) for chronic pancreatitis. We measured the novel beta cell death marker unmethylated insulin ( INS ) DNA in TPIAT recipients before and immediately after islet infusion (n = 21) and again 90 days after TPIAT, concurrent with metabolic functional assessments (n = 25). As expected, INS DNA decreased after pancreatectomy (p = 0.0002). All TPIAT recipients had an elevated unmethylated INS DNA ratio in the first hours following islet infusion. In four samples (three patients), INS DNA was also assessed immediately after islet isolation and again before islet infusion to assess the impact of the isolation process: Unmethylated and methylated INS DNA fractions both increased over this interval, suggesting death of beta cells and exocrine tissue before islet infusion. Higher glucose excursion with mixed‐meal tolerance testing was associated with persistently elevated INS DNA at day 90. In conclusion, we observed universal early elevations in the beta cell death marker INS DNA after TPIAT, with pronounced elevations in the islet supernatant before infusion, likely reflecting beta cell death induced by islet isolation. Persistent posttransplant elevation of INS DNA predicted greater hyperglycemia at 90 days. Abstract : In patients undergoing total pancreatectomy with islet autotransplantation (TPIAT), unmethylated insulin DNA—a biomarker of beta cell death—is elevated immediately after islet isolation and shortly after intraportal infusion, confirming that islet loss occurs in patients undergoing TPIAT for chronic pancreatitis.